Effect of heat shock transcription factor 5(Hsf5) knockdown on heat shock family in mouse Leydig cells and Sertoli cells - ZHONG Lin, ZHONG Hongli, DAI Yujie, ZHANG Qinghua (Jichu yixue yu linchuang, 2023)
Objective To investigate the effect of knockdown heat shock transcription factor 5(Hsf5) on the expression of heat shock family in mouse Leydig cells (TM3) and Sertoli cells(TM4). Methods Mouse TM3 and TM4 cells were cultured and randomly divided into control group and Hsf5 knockdown group. The expression of heat shock transcription factor(HSF) and heat shock protein(HSP) mRNA in the two groups of cells was detected by real-time quantitative PCR. According to the results of RT-qPCR, HSPs with significant differences in the two kinds of cells were selected (P＜0.01). Western blot were used to detect the expression of HSPA2, HSPA5, HSP90ab1 in TM3 cells and HSPA2,HSP90aa1 in TM4 cells. Results Hsf5 knockdown model was successfully constructed by RNA interference. After knockdown of Hsf5, the mRNA expression of Hspa2,Hspa5,Hsp90ab1 in TM3 cells and Hsf2,Hspa2, Hsp90aa1, Hsp90ab1, Hspd1 in TM4 cells was all significantly down-regulated(P＜0.05). In Hsf5 knockdown group, the expression of HSPA2,HSPA5 proteins in TM3 cells and HSPA2 protein in TM4 cells were significantly down-regulated (P＜0.05). Conclusions HSF5 is potentially involved in spermatogenesis by regulating the expression of HSPA2 and HSPA5 in mouse Leydig cells and Sertoli cells.